Evaluation of Efficacy and Safety of Intensive pulse Light (IPL) In Treatment of Hirsutism in Irsutism in Iraqi women with Some Epidemiological Data - Al-Kayalli, Khudhair Khalaf; Al-Qaisy, Mohammed Hussein (Diyala Journal of Medicine, 2019)
Background: Hirsutism is the presence or an excess of terminal (thick and dark) hair growth in women, in a male - like pattern. Hirsutism affects about 5-10% of women during reproductive age. Many therapeutic measures are used in the treatment of hirsutism, which include, drugs therapy and cosmetic measures and this involved self-care methods and laser therapy, of which intensive pulse light is one of useful therapeutic method. Objective: To evaluate the efficacy and safety of intensive pulse light in the treatment of hirsutism with some epidemiological data in Iraqi women. Patients and Methods: A cohort study in which, one hundred and forty seven women with hirsutism of the face (moustache and chin) were seen and evaluated in a laser clinic of Baquba Teaching Hospital, during the period from January 2010 to June 2013, with a mean age of (29.76±9) years . They were examined and evaluated for the grad of hirsutism, type of skin, menstrual cycle, marital status, childbearing, hormonal and steroid therapy and family history of hirsutism. The diagnosis of cause of hirsutism was made by clinical criteria and certain investigations according to the need. They were treated by intensive pulse light (IPL) and anti-hormonal drugs on need, according to the type of skin and severity of the hirsutism and followed up for six months after the end of therapy , the response was graded into four grades, excellent, good , moderate and poor Results: The study revealed that (42.85%) shows an excellent response, (42.17%) with good response, (14.28%) with moderate response and (7.48%) shows a poor response. Severe complications of therapy like blister and hyperpigmentation were rarely seen. The study shows that the idiopathic hirsutism was the common cause of hirsutism of the face (moustache and chin) in women (66.66%), then the polycystic ovary syndrome (24.49%) and hyperprolactenemia (8.85%). Conclusion: We concluded that intensive pulse light was an effective and safe method in treatment of hirsutism in women, whatever the cause and the idiopathic hirsutism was the common cause.